TINDAK PIDANA INTIMIDASI DI INTERNET (CYBERBULLYING) SEBAGAI KEJAHATAN MAYANTARA (CYBERCRIME) - Rachma Rizkyani (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT       Based on freedom of opinion, Indonesian people often misinterpret this freedom. One of irregularity in freedom of opinion is to commit insult through electronic means called cyberbullying. Phenomenon of cyberbullying in other countries has been taken seriously, and there are legal arrangements.       From this background there are two main problems, how to regulate positive criminal law regarding cyberbullying as a form of cybercrime in Indonesia and how to implement cyberbullying crimes under the ITE law. This study uses a qualitative-descriptive method through a normative juridical approach. Data collection techniques is a literature study. Data sources used are a secondary data and primary data. The focus of this research is limited to the legal regulation of cyberbullying in Indonesia and implementation under the ITE law. The results of this study and discussion are that Indonesia has a legal regulation for cyberbullying, With using Law Number 11 of 2008 concerning Information and Electronic Transactions. It can be concluded that legal arrangements can be enshrined cyberbullying with using Article 27 paragraph (3) and (4), Article 28 and Article 29 of Law Number 11 of 2008 about Information and Electronic Transactions. Implementation in Law No. 11 of 2008 concerning ITE has been implemented but there are still many obstacles.ITE Law also regulates procedural law related to investigations carried out by law enforcement officers (police and prosecutors) that provide a new paradigm for law enforcement efforts in order to minimize the potential law for enforcement officers so that it is very useful in providing legal assurance and certainty. Even though the law that regulates cyber crime has been born, in general it has not been able to limit every society's behavior in using the benefits of cyberspace. Cybercrime law inevitably must keep abreast of cybercrime steps one step behind. Keywords: threats / intimidation on the internet is a crime Mayantara.